Fault Detection for Nonlinear Impulsive Switched Systems. (29th July 2013) - Li, Jian; Su, Qingyu; Sun, Lingfang; Li, Bo
Abstract : This paper is concerned with the fault detection problem for nonlinear impulsive switched systems. Fault detection filters are designed such that the augmented systems are stable, and the residual signal generated by the filters achieves the H ∞ -gain for disturbances and guarantees the H - performance for faults. Sufficient conditions for the solvability of this problem are formulated in terms of linear matrix inequalities; furthermore, the filter gains are characterized by a convex optimization problem. A simulation on a continuous stirred tank reactor control system is given to demonstrate the effectiveness of the proposed methods.